2022
DOI: 10.1021/acsnano.2c02014
|View full text |Cite
|
Sign up to set email alerts
|

Observation of an Orientational Glass in a Superlattice of Elliptically-Faceted CdSe Nanocrystals

Abstract: Extensive prior work has shown that colloidal inorganic nanocrystals coated with organic ligand shells can behave as artificial atoms and, as such, form superlattices with different crystal structures and packing densities. Although ordered superlattices present a high degree of longrange positional order, the relative crystallographic orientation of the inorganic nanocrystals with respect to each other tends to be random. Recent works have shown that superlattices can achieve orientational alignment through c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Their Feret diameter 76 is 13.1 nm ±22%, where the different orientations of the faceted NCs with respect to the electron beam likely contribute to their apparent higher size polydispersity. 77 We combine these two types of NCs into superparticles by using our recently developed source-sink emulsion templated assembly procedure. 48 Specifically, we use droplet microfluidics to prepare a monodisperse emulsion of toluene-inwater, the source emulsion, containing the binary dispersion of NCs at a total volume fraction of 0.01%, volumetric ratio of the two NC types of 1:1 or ϕ = 0.5, and NC size ratio γ = 0.70.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their Feret diameter 76 is 13.1 nm ±22%, where the different orientations of the faceted NCs with respect to the electron beam likely contribute to their apparent higher size polydispersity. 77 We combine these two types of NCs into superparticles by using our recently developed source-sink emulsion templated assembly procedure. 48 Specifically, we use droplet microfluidics to prepare a monodisperse emulsion of toluene-inwater, the source emulsion, containing the binary dispersion of NCs at a total volume fraction of 0.01%, volumetric ratio of the two NC types of 1:1 or ϕ = 0.5, and NC size ratio γ = 0.70.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…CdSe/CdS NCs appear faceted likely because of the slow epitaxial growth of the CdS shell on the CdSe core. Their Feret diameter is 13.1 nm ±22%, where the different orientations of the faceted NCs with respect to the electron beam likely contribute to their apparent higher size polydispersity …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…QD solids and films are useful in device fabrication and technology. There has been significant progress to control the structure of self-assembled 2D or 3D QD superlattices for optimized device performance. , Among a range of different self-assembly mechanisms, the self-assembly of QDs at the liquid–air interface has been shown to reproducibly form well-ordered superlattices with high packing densities . Although the structure of these superlattices can be well-controlled, understanding of the photoluminescence properties of these thin films is limited due to the challenge of determining the PLQY and hence Γ r and Γ nr of low volume materials with sufficiently high signal-to-noise ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical assembly of functional inorganic nanoparticles (NPs) into ordered superstructures has attracted increasing attention because the bottom-up strategy provides a robust and promising pathway for the artificial construction of new functional materials and devices with advanced applications in bioimaging, cancer therapy, energy, and information storage. Until now, a rich variety of exquisite and multidimensional superstructures with a highly ordered arrangement or crystalline packing of NPs over sufficiently long distances has been elaborately prepared. Particularly, the fabrication of a three-dimensional (3D) multilayer superlattice film and hollow structures has received significant interest. For instance, Murray et al assembled multicomponent NPs into free-standing binary superlattices via the cocrystallization of two types of NPs, giving a general method of growing centimeter-scale membranes for nanocrystal-based devices . Chen et al reported the development of plasmonic-magnetic hollow vesicles assembled from iron oxide-gold Janus nanoparticles that could generate reactive oxygen species (ROS) and release doxorubicin (DOX) .…”
Section: Introductionmentioning
confidence: 99%